ISLAMIC VALUES AND LOCAL WISDOMS MANIFESTED AS STUDENTS' SOFT SKILLS FOR SOCIETY 5.0 - Idha Nurhamidah; Sugeng Purwanto (Universitas 17 Agustus 1945 Semarang, 2020)
The current study reports Year One of a Two-Year Research Project on manifestation of Islamic values and local wisdoms to anticipate Society 5.0. A survey questionnaire was administered to 39 subjects consisting of students of Sultan Agung Islamic University Semarang enrolled in Basic Culture Course in order to grasp their profiles in terms of S (Strength) W (Weakness) O (Opportunity) and T (Threat) with respect to Islamic values and local wisdoms. It turns out that all students show their strength, namely being aware of the Islamic values and local wisdoms positively contributing to the success of the future career as soft skills. However, their weakness is that they master knowledge of Islamic values and local wisdoms only at cognitive level. In practice rules are violated. Opportunity is open for them since they are still at college with rooms for advancement and improvement. Meanwhile, the threat is that they may be influenced by the negative impact of cyber information providers within disruption of digital manufacture unless it is anticipated by equipping them with manifestation of Islamic values and local wisdoms to successfully survive in Society 5.0 in which people shall govern technology and not otherwise. Keywords: Islamic values, local wisdoms, soft skills, society 5.0, digital manufacture